Konstruksi Hukum Unsur Mens Rea Dan Kerugian Keuangan Negara Dalam Tindak Pidana Korupsi Pada Badan Usaha Milik Negara (BUMN): Legal Construction of State Financial Loss and the Implementation of the Business Judgment Rule in Act Number 16 of 2025 - Beniharmoni Harefa; Siswanto Siswanto (Faculty of Law, Maranatha Christian University, 2026)
State-Owned Enterprises (SOEs) hold a strategic position in the national economic as both economic actor and instruments of the state in promoting public welfare. However, this position gives rise to juridical complexities, particularly concerning directors’ liability for corporate losses that are often classified as state financial losses. This issue has become more prominent following the enactment of Law Number 16 of 2025 on SOEs, which not only strengthens corporate governance but also clarifies the boundary between business risk and unlawful conduct. This research aims to analyze the relationship between mens rea, state financial losses, and corruption offenses within the newly established legal framework governing SOEs, as well as to examine the application of the BJR in limiting the criminalization of business decisions. The research employs a normative juridical method with statutory, case, comparative, and conceptual approaches. The findings indicate that not all losses incurred by SOEs can be classified as state financial losses in the criminal law sense. Criminal liability requires the cumulative fulfillment of state loss, unlawful conduct, and mens rea. In this context, the BJR serves as a legal protection mechanism for directors who act in good faith, with due care, and without conflict of interest, while maintaining a balance between legal certainty, accountability, and managerial discretion